Membrane Technology Application for Fractionation Process to Obtain High Quality Glucosamine - Nur Rokhati; Titik Istirokhatun; Nur ‘Aini Hamada; Dwi Titik Apriyanti (Reaktor, 2020)
Glucosamine, monosaccharide from chitosan obtained from the chitin deacetylation process, has been used widely in various fields such as nutrition, pharmacy, and cosmetics. Glucosamine can be obtained from the hydrolysis of chitosan. Enzymatic hydrolysis provides the advantage of mild reaction conditions, environmentally friendly, and high yield. But until now, the separation of glucosamine from the chitosan hydrolysis fraction has been an obstacle. Ultrafiltration membranes offer an efficient filtration process because they do not require additional chemicals. The performance of ultrafiltration membranes was analyzed from the fractionation process of chitosan hydrolysis. The PES membranes in 10, 25, and 50 kDa were used to filter hydrolyzed Low Molecular Weight Chitosan (LMWC) in varied concentrations. The experiment was carried out in crossflow membrane module for flat sheet at room temperature in 1 bar. The permeate flux during filtration decreased rapidly at the initial and gradually over time because of fouling and concentration polarization. The more concentrated hydrolyzed LMWC solution resulted higher percentage of rejection up to almost 20% at the same membrane MWCO while higher MWCO resulted lower rejection percentage for the same hydrolyzed LMWC concentration. The FTIR spectrum of the used membranes of all types had absorption bands of glucosamine which proved that the fractionation process occurred. The time retention in HPLC chromatograms of glucosamine produced were similar with standard glucosamine. Thus, ultrafiltration could be applied for hydrolyzed LMWC fractionation process.Keywords: fractionation; glucosamine; LMWC; MWCO; ultrafiltration